Professionals’ Dichotomous Take on Instructional Supervision Styles for Technical Institutions in Ghana - Y D, Quansah Joseph; John, Gayomey; Elvis, Attakora-Amaniampong (European Scientific Journal, ESJ, 2016)
Learning is central to the purpose of a school and teaching is a basic tool to promote learning. This, then underlines the significance of instructional supervision and its types as magic bullet to effective teaching and learning in most educational institutions. However, contemporary research within the Ghanaian context is salient on the professionals’ preferred supervision types in public technical educational institutions. This study employed a descriptive research survey design to accomplish this. Three set of questionnaires were developed after literature survey and data was collected from 502 participants consisting of 484 teachers, 9 circuit supervisors and 9 principals. These participants were selected based on a multi-stage sampling technique, from the nine Technical Institutions in the Greater Accra region. The data, mainly categorical in nature was analysed using mean and percentages with the aid of SPSS version 18. The findings of the study showed that teachers preferred instructional supervision that is premised on the mutual relationship between the teachers and the supervisors while principals and external supervisors preferred the formal rules-based supervision. This study suggests a hybrid instructional supervision which merges the two types of instructional supervision. The formal rules-based and collegial based types of instructional supervision, if teachers’ performance are to be enhanced.